2017
DOI: 10.1002/2016jg003493
|View full text |Cite
|
Sign up to set email alerts
|

Modeling rates of DOC degradation using DOM composition and hydroclimatic variables

Abstract: The fluvial fluxes of dissolved organic carbon (DOC) from peatlands form an important part of that ecosystem's carbon cycle, contributing approximately 35% of the overall peatland carbon budget. The in‐stream processes acting on the DOC, such as photodegradation and biodegradation, can lead to DOC loss and thus contribute CO2 to the atmosphere. The aim of this study was to understand what controls the rates of DOC degradation. Water samples from a headwater, peat‐covered catchment, were collected over a 23 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Additionally, there is some evidence that some LMW compounds (such as those with carboxylic functional groups) might elute with higher molecular weight compounds with similar functional groups during size‐exclusion chromatography (Ruhl & Jekel, ). Previous studies have also reported rapid depletion of soil‐derived small molecular weight compounds, such as carboxylic acids and other high H/C and N compounds in small headwater streams (Berggren et al, ; Drake et al, ; Moody & Worrall, ), which have been suggested to fuel the bulk of microbial metabolism in these systems (Berggren et al, ). Our results would suggest that most of these soil‐derived, highly labile substrates are actually depleted at the soil‐stream interface and that only a small proportion actually reach the stream channel to fuel bacterial metabolism there.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, there is some evidence that some LMW compounds (such as those with carboxylic functional groups) might elute with higher molecular weight compounds with similar functional groups during size‐exclusion chromatography (Ruhl & Jekel, ). Previous studies have also reported rapid depletion of soil‐derived small molecular weight compounds, such as carboxylic acids and other high H/C and N compounds in small headwater streams (Berggren et al, ; Drake et al, ; Moody & Worrall, ), which have been suggested to fuel the bulk of microbial metabolism in these systems (Berggren et al, ). Our results would suggest that most of these soil‐derived, highly labile substrates are actually depleted at the soil‐stream interface and that only a small proportion actually reach the stream channel to fuel bacterial metabolism there.…”
Section: Resultsmentioning
confidence: 98%
“…Here, I suggest that this could result from stream respiration alone accounting for 23% ± 11% of the annual total inputs of DOC in a first order stream, assuming implicitly that sunlight and other potential processes did not play a significant role (see below). More DOC losses will occur downstream through the whole network (Raymond et al ; Bertuzzo et al ; Moody and Worrall ). The stream efficiency to mineralize carbon will be much lower under very high flows (not part of this study) where POC losses are likely to be significant contributors to the carbon flux.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be the case (e.g., Dawson et al 2001;Dawson et al 2002), but at least the metabolic rates and hydrological behaviors were found to be similar in two independent streams with significant lateral inflows and the upscaling was limited to the same stream order. Further studies should explore the downstream effects through the river network (e.g., Raymond et al 2016;Bertuzzo et al 2017;Moody and Worrall 2017;Ulseth et al 2018).…”
Section: Upscalingmentioning
confidence: 99%
“…These rates of pool “turnover” may be important for peatland chemistry and peat accumulation rates (Beer & Blodau, ; Morris & Waddington, ) and for understanding aquatic carbon fluxes from peatlands with pools, particularly if the carbon processing is different between natural and artificial pool systems. Pools with longer water residence times may be subject to enhanced photochemical processing of dissolved organic carbon (e.g., Pickard, Heal, McLeod, & Dinsmore, ; all pools were ≤50 cm deep); hence, the quality of dissolved organic carbon may vary between pools, which could be important for downstream water treatment for potable supply (Moody & Worrall, ; Worrall & Burt, ). On the other hand, the slower turnover of water in some larger pools may mean that the remaining carbon is largely recalcitrant, and little further processing can occur, whereas in smaller pools, processing of carbon can continue for longer periods if the pool water volume is replaced more frequently.…”
Section: Discussionmentioning
confidence: 99%